Improvement method for shield muck of muddy soft soil stratum

By using materials such as metakaolin, blast furnace slag and other materials to prepare base materials in the construction of silt soft soil formation shields, and combining flocculants and other substances to form a gel system, the problem of poor plasticity of slag flow is solved, and effective improvement of slag and construction safety is achieved.

CN119613026APending Publication Date: 2025-03-14EAST CHINA JIAOTONG UNIVERSITY

Patent Information

Application Number
CN202411903629.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

It is difficult for silty soft soil strata to form good fluid plasticity during shield construction, resulting in the inability to effectively transport the slag, which may cause gushing and harm construction personnel and equipment.

Method used

The base material is prepared by metakaolin and blast furnace slag, and lignin sulfonate, nanosilica powder, sodium hydroxide solution, sodium silicate solution and anionic polyacrylamide are added to form a gel system through stirring and flocculation, which improves the fluidity and stability of the slag.

Benefits of technology

Effectively reduce the moisture content of slag, improve its solid-liquid separation efficiency, prevent gushing, ensure construction safety, and at the same time, it is low in cost, and is suitable for on-site preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613026A_ABST
    Figure CN119613026A_ABST
Patent Text Reader

Abstract

The invention discloses an improvement method of sludge soft soil layer shield muck, and belongs to the technical field of shield tunnel construction muck improvement. Metakaolin, blast furnace slag, lignosulfonate and nano silicon dioxide powder are mixed to prepare a mixed raw material, the mixed raw material is pumped into a muck bin, then an alkali-activated solution is pumped into the muck bin, and the mixed raw material is stirred to be uniform; and after mixing and stirring, adding anionic polyacrylamide powder and bentonite, and continuously stirring until a gel system is generated, thereby completing muck improvement. According to the invention, sodium hydroxide and sodium silicate are used as alkali-activated solutions to activate a gel system, blast furnace slag provides a large amount of silicon elements and aluminum elements, and metakaolin contains silicon, aluminum and calcium elements to improve the strength of the gel system; during use, the two raw materials are separated, so that the two raw materials are prevented from reacting in advance before reaching a muck bin to generate gel, and pipeline blockage is avoided; the anionic polyacrylamide and the bentonite are matched, so that the permeability is improved, the drainage of water is facilitated, and the occurrence of spewing is effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shield tunnel construction debris improvement, in particular to a method for improving shield tunnel debris in a silty soft soil layer. Background Art

[0002] Shield construction is one of the important means of urban underground space development. The principle of earth pressure balance shield construction is to balance the soil pressure inside the excavation face cutout with the soil pressure outside the cutter head of the excavation face. Therefore, the medium of the excavation face is required to maintain good flow plasticity, but not all soil layers can meet the conditions for shield construction.

[0003] Silt soft soil is widely distributed in China, but due to the easy separation of water and soil in water-rich strata, loose soil and poor stability, it is difficult to form soil with good plasticity when using earth pressure balance shield. If the plasticity of the soil is not well improved, the soil will not be able to effectively form a soil plug at the screw conveyor, which will cause the torque of the force plate to increase and the soil discharge to be difficult, or the water pressure at the discharge port is too high, resulting in gushing. The above problems are extremely harmful to both construction personnel and construction equipment.

[0004] At present, the gushing problem is mainly solved from two aspects: one is through the process optimization of the slag improvement technology. The invention patent with publication number CN107987839A and titled "A slag improver for shield construction in water-rich sand layer and its construction method" uses bentonite as the raw material, which has a high cost and its construction method is relatively complicated; the second is through the upgrading and transformation of the shield excavation equipment. The new patent with publication number CN215860199U and titled "A Shield Machine Screw Conveyor Anti-Gushing Device" has the scraping components and positioning components easily get stuck by gravel, stones, etc., causing component failure, posing huge safety hazards to the construction.

[0005] Existing methods for improving slag are not suitable for improving and reinforcing silty soft soil layers. Based on this, in order to better solve the gushing problem of slag related to silty soft soil layers, and the problem that conventional improvers will coagulate in advance before entering the soil bin, resulting in pipeline blockage, premature coagulation of mud, and improvement failure, the present invention proposes a method for improving shield slag in silty soft soil layers. Summary of the invention

[0006] The purpose of the present invention is to provide a method for improving shield slag in silty soft soil strata to solve the problems in the background technology.

[0007] To achieve the above object, the present invention provides a method for improving shield slag in silty soft soil strata, comprising the following steps: S1. Put metakaolin and blast furnace slag in a stirrer, add clean water and stir continuously for 15-20 minutes to prepare a base material; S2. After the base materials are evenly mixed, lignin sulfonate and nano-silicon dioxide powder are added, and stirring is continued for 15 to 30 minutes. After standing, a mixed raw material is obtained; S3, inject clean water into the polymer stirring box, slowly add sodium hydroxide solution, continue stirring until the heat release is complete, slowly add sodium silicate solution, continue stirring for 15 to 20 minutes, and prepare an alkali-activated solution after standing; S4. First, pump the mixed raw materials into the slag bin, then pump the alkali-activated solution into the slag bin, mix and stir with the slag for 15 to 20 minutes, slowly add anionic polyacrylamide powder and bentonite, and continue stirring until a gel system is produced to complete the slag improvement.

[0008] Preferably, in S1, the metakaolin is obtained by calcining kaolin at 700° C. and sieving.

[0009] Preferably, in S1, the base materials are, by percentage, 15% to 20% metakaolin, 35% to 40% blast furnace slag, and 40% to 60% clean water.

[0010] Preferably, in S2, the mixed raw materials are calculated by percentage: the base material is 80% to 90%, the lignin sulfonate is 1% to 5%, and the nano-silicon dioxide powder is 5% to 20%.

[0011] Preferably, in S3, the mass ratio of the sodium hydroxide solution to the sodium silicate solution is 4-7:1.

[0012] Preferably, in S4, by percentage, the amount of the alkali-activated solution added is 20% to 30%, the amount of the mixed raw material added is 50% to 70%, the amount of the anionic polyacrylamide added is 3% to 8%, and the amount of the bentonite added is 5% to 20%.

[0013] Preferably, in S4, before pumping the mixed raw materials, the stirring device in the stirrer is turned on to stir the mixed raw materials evenly, and then the mixed raw materials are pumped into the shield bentonite tank and continuously stirred in the tank; at the same time, the stirring device in the polymer stirring box is turned on to continuously stir the alkali-excited solution.

[0014] Preferably, in S4, a small amount of cellulose material is added into the slag bin to enhance the cohesion of the slag.

[0015] Therefore, the present invention discloses a method for improving shield slag in silty soft soil strata, which has the following beneficial effects: (1) In the present invention, sodium hydroxide solution and sodium silicate solution are mixed as an alkaline activating solution to activate the gel system. Blast furnace slag provides a large amount of silicon and aluminum elements. Metakaolin contains silicon, aluminum and calcium elements, which can improve the strength of the gel system. When used, the two raw materials are separated to avoid premature reaction before reaching the soil bin to produce gel, resulting in pipeline blockage, thereby solving the problem of premature coagulation of mud and improvement failure during slag improvement.

[0016] (2) The raw materials in the present invention are easy to obtain, the gel system is easy to prepare, suitable for preparation at the construction site, and the improvement cost is low. Blast furnace slag and high-altitude land are easy to obtain, which overcomes the inherent calcium deficiency of fly ash. No other products need to be added, which saves costs. At the same time, it contains a small amount of sulfur and is more environmentally friendly. Anionic polyacrylamide is a highly efficient flocculant. It can aggregate fine particles in the slag through charge neutralization and bridging, thereby accelerating sedimentation and improving solid-liquid separation efficiency. The present invention can effectively reduce the water content of the slag and reduce its fluidity through the dual effects of flocculation and solidification. After the fine particles in the slag are aggregated by the flocculant, the porosity of the soil can be increased, thereby improving its permeability, which is conducive to the discharge of water, thereby effectively preventing the occurrence of gushing and ensuring construction safety.

[0017] (3) The present invention also adds nano-silicon dioxide, bentonite and lignin sulfonate during the improvement process. Nano-silicon dioxide has extremely high specific surface area and activity, which can significantly improve the gelling properties and mechanical strength of the soil, and at the same time improve the microstructure of the soil and improve its permeability; bentonite has strong water absorption and swelling properties, which can increase the adhesion of the soil, and at the same time improve the permeability of the soil and make it more uniform; lignin sulfonate can increase the porosity of the soil, improve the air permeability and water permeability of the soil, reduce the compaction of the soil, enhance the binding force between soil particles, and improve the stability and anti-erosion ability of the soil. The technical scheme of the present invention is further described in detail below through the accompanying drawings and examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a flow chart of Embodiment 1 of the present invention; Figure 2 The present invention performs morphology detection on the slag of Example 1 after curing Figure 1 ; Figure 3 The present invention performs morphology detection on the slag of Example 1 after curing Figure 2 . DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0020] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0021] Example 1 This embodiment provides a method for improving shield slag in silty soft soil strata, such as Figure 1 As shown, the specific steps include: S1. Using metakaolin and blast furnace slag to prepare a base material, specifically: calcining kaolin at 700° C., collecting the generated metakaolin, and crushing the blast furnace slag into powder; adding a certain amount of clean water into the stirrer, turning on the device to allow the water flow to be in a flowing state, slowly adding metakaolin and blast furnace slag, and continuously stirring for 15 minutes, wherein the metakaolin is 15%, the blast furnace slag is 35%, and the clean water is 50%, to obtain the base material; S2. After the base material is evenly mixed, lignin sulfonate and nano-silicon dioxide powder are added, and the base material is 85%, lignin sulfonate is 5%, and nano-silicon dioxide powder is 10%. The mixture is stirred for 30 minutes and allowed to stand to obtain a mixed raw material; S3. Pour clean water into the polymer stirring box, slowly add sodium silicate solution and sodium hydroxide solution in sequence, and continue stirring until the heat release is complete. The mass ratio of sodium hydroxide solution to silicon carbide solution is 6:1. Continue stirring for 15 minutes, and prepare an alkali-activated solution after standing. S4. Turn on the stirring device in the stirrer to stir the base material evenly, then pump the base material into the shield bentonite tank and continue stirring in the tank; at the same time, turn on the stirring device in the polymer stirring box to continuously stir the alkali-activated solution; then pump the mixed raw materials into the soil bin in front of the cutterhead of the shield machine, and then pump the alkali-activated solution polymer pipeline into the slag bin, mix and stir with the slag for 15 minutes, and slowly add anionic polyacrylamide powder and bentonite, wherein, by percentage, the addition amount of alkali-activated solution is 25%, the addition amount of mixed raw materials is 55%, the addition amount of anionic polyacrylamide is 8%, and the addition amount of bentonite is 12%; continue stirring until a gel system is produced to complete the slag improvement.

[0022] Example 2 The steps are the same as those in Example 1, except that the addition ratio of each substance in S4 is modified to 20% of the alkaline excitation solution, 65% of the mixed raw material, 5% of the anionic polyacrylamide, and 10% of the bentonite.

[0023] The improvement effects of Examples 1 and 2 were tested, and the results of the high water pressure penetration test and the on-site slump test were analyzed to show that after the soil samples taken from the site (muddy soft soil layer) were uniformly stirred and mixed using the methods of Examples 1 and 2, the slump could be controlled within 20 cm; Under the 2.5 bar (i.e. 25 m head) water pressure test, the permeability coefficient of the improved slag reached 1×10 -7 m / s, lasting for more than 4 hours and less than the critical value of eruption 1×10 -5 m / s, proving that the method protected by the present invention has a good effect on improving the slag.

[0024] Comparative Example 1 The steps are the same as those in Example 1, except that the method of adding the alkali-activated solution and the mixed raw material in S4 is changed to mixing the alkali-activated solution and the mixed raw material before pumping them into the soil bin, and then pumping the mixture into the bin.

[0025] The improvement effect of comparative example 1 was tested, and it was found that the alkali-activated solution and the base material reacted to form a gel system in the soil bin when entering the slag, and cement separation occurred, which blocked the pipeline. Only a small amount entered the soil bin, and the improvement effect of the slag was not as good as that of Examples 1 and 2.

[0026] Comparative Example 2 The steps are the same as those in Example 1, except that the anionic polyacrylamide and bentonite added in S4 are removed.

[0027] The improvement effect of Comparative Example 2 was tested by high water pressure penetration test. Compared with Example 1, the slump of Comparative Example 2 was reduced; because of the lack of anionic polyacrylamide, its flocculation effect was weakened, and the lack of the swelling effect of bentonite caused the fluidity of the slag to deteriorate.

[0028] Under a 2.5 bar (i.e., 25 m head) water pressure test, the permeability coefficient of the improved slag increases compared to Example 1, because the flocculation and expansion effects are weakened, the gaps between the particles are enlarged, and the water permeability is enhanced.

[0029] Its critical value of eruption is lower than that of Example 1. Due to the lack of anionic polyacrylamide and bentonite, its adsorption and adhesion are weakened, the stability of the slag is reduced, eruption is more likely to occur, and the critical value of eruption is reduced.

[0030] In addition, the improved slag in Example 1 was cured for 28 days, and the morphology of the samples was tested after the curing. Figure 2 , 3 As shown, magnified 1000 times Figure 2It can be seen that the pores on the surface of the slag are basically filled with hydration products, the connection between soil particles gradually changes from contact connection to cementation connection, and the pores between particles are also decreasing. Figure 3 It can be seen that the surface of the soil particles has been covered by most of the cementing material, and needle-shaped calcium aluminate crystals are formed between the particles. At the same time, a large amount of flocculent CSH gel can be observed. In this process, the hydration products are cemented with each other.

[0031] The above comparison and detection can illustrate that the method protected by the present invention has a certain improvement effect on the slag, making the soil structure more compact.

[0032] Therefore, the invention discloses a method for improving shield slag in a silty soft soil layer. Sodium hydroxide and sodium silicate are used as alkaline excitation solutions to activate the gel system. Blast furnace slag provides a large amount of silicon and aluminum elements. Metakaolin contains silicon, aluminum and calcium elements, which can improve the strength of the gel system. The two raw materials are separated during use to avoid premature reaction between the two materials to produce gel before reaching the slag bin, which causes pipeline blockage. Anionic polyacrylamide and bentonite are used in combination to improve the permeability, which is beneficial to the discharge of water, thereby effectively preventing the occurrence of gushing.

[0033] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for improving shield slag in silty soft soil, characterized in that: The following steps are involved: S1. Put metakaolin and blast furnace slag in a stirrer, add clean water and stir continuously for 15-20 minutes to prepare a base material; S2. After the base materials are evenly mixed, lignin sulfonate and nano-silicon dioxide powder are added, and stirring is continued for 15 to 30 minutes. After standing, a mixed raw material is obtained; S3, inject clean water into the polymer stirring box, slowly add sodium hydroxide solution, continue stirring until the heat release is complete, slowly add sodium silicate solution, continue stirring for 15 to 20 minutes, and prepare an alkali-activated solution after standing; S4. First, pump the mixed raw materials into the slag bin, then pump the alkali-activated solution into the slag bin, mix and stir with the slag for 15 to 20 minutes, slowly add anionic polyacrylamide powder and bentonite, and continue stirring until a gel system is produced to complete the slag improvement.

2. The method for improving shield slag in muddy soft soil according to claim 1, characterized in that: In S1, the metakaolin is obtained by calcining kaolin at 700° C. and sieving.

3. The method for improving shield slag in muddy soft soil according to claim 1, characterized in that: In S1, the base materials are, by percentage, 15% to 20% of metakaolin, 35% to 40% of blast furnace slag, and 40% to 60% of clean water.

4. The method for improving shield slag in muddy soft soil according to claim 3, characterized in that: In S2, the mixed raw materials are calculated by percentage: the base material is 80% to 90%, the lignin sulfonate is 1% to 5%, and the nano-silicon dioxide powder is 5% to 20%.

5. The method for improving shield slag in muddy soft soil strata according to claim 1, characterized in that: In S3, the mass ratio of the sodium hydroxide solution to the sodium silicate solution is 4-7:

1.

6. The method for improving shield slag in muddy soft soil according to claim 1, characterized in that: In S4, by percentage, the addition amount of the alkali excitation solution is 20% to 30%, the addition amount of the mixed raw material is 50% to 70%, the addition amount of the anionic polyacrylamide is 3% to 8%, and the addition amount of the bentonite is 5% to 20%.

Citation Information

Patent Citations

  • Anti-gushing device for spiral conveyor of shield tunneling machine

    CN215860199U

Cited By

  • Shield muck improvement method for water-rich coarse-particle stratum

    CN121205643A